2004
DOI: 10.1002/ajim.20071
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity pain and computer use among engineering graduate students

Abstract: Background: The objective of this study was to investigate risk factors associated with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
4
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 6 publications
(8 reference statements)
7
54
4
2
Order By: Relevance
“…Several studies among college students have noted a female preponderance in the prevalence of MSDs 6,7,14,17 . However, no significant sexual differences were observed in all three domains of this study (i.e point-, period-prevalence and severity).…”
Section: African Health Sciences Vol 15 Issue 2 June 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies among college students have noted a female preponderance in the prevalence of MSDs 6,7,14,17 . However, no significant sexual differences were observed in all three domains of this study (i.e point-, period-prevalence and severity).…”
Section: African Health Sciences Vol 15 Issue 2 June 2015mentioning
confidence: 99%
“…They are a major cause of severe long-term pain and disability 1,2 , productivity loss 3 and reduced quality of life 4,5 which can lead to reduced educational attainment among students. In recent years, MSDs have emerged as a public health problem among college students, with the estimated prevalence rate varying between 32.9% and 89.3% in different parts of the world [6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Factors such as computer usage [10][11][12][13]17 , female sex 6,7,14,17 , lack of regular exercise 13,18 and psychosocial stress and mental pressure 6,15 have been associated with increased prevalence of MSDs among this population.…”
Section: Introductionmentioning
confidence: 99%
“…Schlossberg, Morrow, Llosa 16 and Shantakumari, Eldeeb, Sreedharan 17 mention that improper ergonomics manifest even before students reach graduation.…”
Section: Methodsmentioning
confidence: 99%
“…Laptop computers are ideal for student use because of their small size and portability. A questionnaire administered by Schlossberg et al (2004) revealed that 34% of first year graduate students report using a computer for greater than 40 hours per week, and 80% use their computer for greater than 20 hours per week. The proportion of students using a computer to the same extent in their fifth year of graduate study increased to 56% and 95% respectively.…”
Section: Risk Factors Associated With Laptop Computer Usementioning
confidence: 99%
“…consequently, musculoskeletal discomfort associated with computer use is widespread in college students, with over 50% reporting some form of discomfort (Jenkins et al, 2007;Schlossberg et al, 2004). These factors make college students a particularly important population to examine in terms of understanding the risks and attempting to find solutions.…”
Section: Current Directionmentioning
confidence: 99%